Conducta de densificación en frío de mezclas Cu-Al y Cu-Al-SiC procesadas por molienda de alta energía - Ramírez Vinasco, Deisy (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
This work involves the preparation of Cu-Al-SiC composite powders by a high-energy milling process and the study of their densification behavior by cold compaction. The goal of the milling process is to get embedded the ceramic particles in the metal matrix to enhance the distribution of the metal and ceramic phases in the compacts, an important condition to derive in isotropic properties of consolidated materials. For comparison purposes, compressibility tests of a Cu-5Al matrix prepared by high energy milling were performed; while additions of 1, 5 and 10 wt.% SiC were added to the matrix. It was found that the high-energy milling process effectively leads to Cu-Al-SiC composite powders with a homogeneous distribution of the reinforcement in the matrix. Compressibility essays showed that densification of the powders decreased with the reinforcement content; a densification of 73.7% was obtained for composites with 10% SiC compared to 76.0% for samples with 1% SiC at the maximum load applied. Milling time reduced the plastic deformation capacity of the matrix leading to fracture of the cold welded aggregates; the fracture process was accelerated by the addition of hard reinforcement particles. Thus, morphology of the powders changed from laminar, to fine fragments and coarse aggregates, affecting the compaction behavior.

Estudios de tecnología de polvos ofrecen modelos que definen el comportamiento de compactación de sistemas frágiles y/o dúctiles, pero no existen modelos que definan la compresibilidad de una mezcla metal-cerámico. El principal objetivo de este trabajo de investigación es proponer un modelo que explique la conducta de densificación en frío en el sistema Cu-Al-SiC. Este trabajo envuelve la preparación de mezclas Cu-5Al y Cu-Al-SiC por un proceso de molienda mecánica de alta energía y la evaluación del grado de densificación en frío por curvas de compresibilidad en la obtención de compactos densos. El propósito de usar molienda mecánica de alta energía es embeber las partículas cerámicas en la matriz metálica para mejorar la distribución de fases, condición importante para lograr propiedades isotrópicas en materiales consolidados por sinterización. La función de la fase cerámica es reducir la densidad y el coeficiente de disipación térmica del material, mientras que la matriz es modificada con aluminio para disminuir su densidad y la temperatura de sinterización. La conducta de densificación de mezclas Cu-Al-SiC se estudió usando tres cantidades de refuerzo y se compara con la matriz Cu-5Al.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2013-1909; Densificación; Frío de mezclas; Molienda; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5202